Impact of influent characteristics and operational parameters on nitrous oxide emissions in wastewater treatment: Strategies for mitigation and microbial insights - Yi-Wei Zhao; Li-Li Du; Bing Hu; Hong-Yong Lin; Bin Liang; Yun-Peng Song; Yu-Qi Wang; Hong-Wu Wang; Peng-Fei Li; Ai-Jie Wang; Hong-Cheng Wang (Current Research in Biotechnology, 2024)
Nitrous oxide (N2O) emissions from the wastewater treatment sector are a significant contributor to global greenhouse gas levels. This investigation delves into the mechanisms of N2O generation and uptake, correlating microbial processes with variables such as influent characteristics and operational parameters. The nature of carbon substrates in the influent profoundly influences microbial consortia and N2O output. Elevating the carbon-to-nitrogen (C/N) ratio has been shown to curtail N2O emissions by alleviating the competitive dynamics among denitrifying enzymes. Optimal activity of N2O reductase is achieved by maintaining a neutral to mildly alkaline pH and stable ambient temperatures. It is imperative to circumvent extreme aeration rates and prolonged aeration periods to reduce N2O release. The study underscores the importance of an effective carbon feed strategy and advocates for prolonged hydraulic retention times (HRT) and sludge retention times (SRT) in activated sludge suspension systems to inhibit N2O escape. Notably, excessive internal recycling, coupled with heightened dissolved oxygen (DO) levels in aerobic zones, intensifies N2O emission risks. Moreover, the presence of hazardous contaminants, such as heavy metals and antibiotics, interferes with nitrogen elimination processes, warranting a comprehensive assessment of consequent N2O emission hazards. This research provides a scientific basis as well as practical management approaches to diminish N2O emissions.